High strength self-compacting concrete with recycled aggregates - Chng, Sam Xian Ming. (2011)
In recent years, great emphasis has been given to sustainability due to the decreasing of natural resources and the destruction of nature. In order to achieve environmental sustainability, there must be improved productivity especially in the big scale construction industry. The paper reports the production of high-strength self-compacting concrete using recycled concrete aggregates (RCA) for structural application. The use of RCA to fully replaced natural aggregates is investigated. The feasibility of using RCA was tested by conducting experiments on the strength and durability of the concrete. The desired strength was achieved and the modulus of elasticity was found to be within acceptable range. This thesis will open up the possibility of cleaner and greener concrete for the environment.